2017
DOI: 10.1097/adm.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mindfulness-Based Parenting on Women in Treatment for Opioid Use Disorder

Abstract: Study findings suggest a trauma-informed MBP intervention for parenting women with opioid use disorders is associated with significant clinical improvements in quality of parenting behavior. Results of this model show promise in supporting parenting of mothers receiving treatment for opioid use disorders to enhance bonding and parenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…[57][58][59] Previous research of a group-based mindful parenting intervention for this population demonstrated promising results in improving maternal stress and parenting. 60,61 Patient-centered medical homes may improve WCC adherence through better patient outreach, care coordination, and provider continuity. 62 Home visiting programs have also shown potential to increase WCC adherence among low-income families.…”
Section: Gaps In Wccmentioning
confidence: 99%
“…[57][58][59] Previous research of a group-based mindful parenting intervention for this population demonstrated promising results in improving maternal stress and parenting. 60,61 Patient-centered medical homes may improve WCC adherence through better patient outreach, care coordination, and provider continuity. 62 Home visiting programs have also shown potential to increase WCC adherence among low-income families.…”
Section: Gaps In Wccmentioning
confidence: 99%
“…Our findings demonstrate that emotion regulation serves as an important mediating mechanism for genetic influences on maternal behavior, suggesting the promise of targeting emotion regulation deficits in prevention and intervention efforts aimed at promoting sensitive maternal behaviors, particularly among those genetically and/or environmentally at risk. For example, recent research has shown that mindfulness-based parenting intervention is effective in improving parenting quality among mothers, particularly among those who experienced higher childhood adversity (Gannon, Mackenzie, Kaltenbach, & Abatemarco, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with best practices for assessing outcomes for parenting interventions reviewed by Powell (2013), the use of a comparison group is best practice, allows for stronger inferences, and facilitates the translation of research to practice. Another example is a trauma-informed mindfulness intervention for parents with OUD that found that the intervention was associated with improvements in quality of parenting behaviors, especially for mothers with higher baseline adverse childhood experiences (Gannon, Mackenzie, Kaltenbach, & Abatemarco, 2017), highlighting the need to consider a parent's own adverse childhood experiences when delivering parenting interventions for parents with OUD.…”
Section: Testing Existing Interventions In Effectiveness Trialsmentioning
confidence: 99%